DIMENSI KEISLAMAN MASYARAKAT BANTEN PADA PRAKTIK TAREKAT QADIRIYAH NAQSYABANDIYAH - Abdullah, Wawan; Ma'mur, Ilzamudin; Gunawan, Agus; Syam, Ahmad Bazari (Universitas Islam Madura, 2024)
The study of the Qadiriyah congregation in Banten needs to be explored and known through study and research. This research uses a qualitative method with a library study approach, data collection techniques through books, journals, magazines, reports and written sources that are relevant to the research. The research results show that: 1) suluk is the initial process of knowing God. 2) dhikr which is strengthened in qadariyah chanting is the reading of monotheism sentences in different ways taught by the teacher. 3) read prayers; The Qadiriyah Order uses